Early Aggression and Later Delinquency: Considering the Redirecting Role of Good Parenting. (October 2017) - Hay, Carter; Meldrum, Ryan C.; Widdowson, Alex O.; Piquero, Alex R.
Childhood aggression consistently predicts delinquency during adolescence, but research in this area reveals exceptions, with some highly aggressive children becoming relatively nondelinquent adolescents. This directs attention to the factors that explain why early aggression is sometimes not followed by later delinquency. This study considers that parenting marked by attachment, consistent monitoring, and the avoidance of harshness and hostility may be one such factor. This is considered with data from a sample of roughly 800 U.S. families, with analyses focused on 217 youth who were highest in aggression at 4–7 years of age. The analysis revealed substantial variation among aggressive youth in the quality of parenting that they received from ages 9 to 12. This variation helped explain variation in age 15 delinquency, with this relationship being mediated by adolescent levels of school bonds, susceptibility to peer pressure, and low self-control. We discuss the implications of these findings for theory, future research, and policy efforts to reduce delinquency among aggressive and antisocial children.